Launching prosocial crowdfunding campaigns: The final countdown - Duarte, F.; Emanuel-Correia, R.; Tomé, S.; Gama, A. P. M. (Emerging Markets Finance and Trade, 2024)
Prosocial crowdfunding has achieved a growing audience by providing a financing source for entrepreneurs in the microfinance space. Using data from Kiva, a leading prosocial crowdfunding platform, we examined whether there is a right time to launch a crowdfunding campaign. This is the first study to unravel the role of temporal patterns in securing funds in emerging markets. Our results indicate a reverse turn-of-the-month effect on the fully funded campaigns. We further identified a “positive winter prosocial effect” and a “positive first-half-of-the-week effect” on successful fundraising. As such, our study highlights relevant similarities between financial markets and crowdfunding.